STRATEGI PEMASARAN PAKET WISATA MELALUI MEDIA ONLINE DI TRULY ASIA TOUR AND TRAVEL - Prawita Sari, Ade; Kusuma Negara, I Made; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
The purpose of this research is to find out the marketing strategy of tour package at Truly Asia tour and travel through online system. SWOT analysis is the method for this research and implemented into SWOT matrix table to find out the right strategy for the tour package at Truly Asia tour and travel through online system. Now days Marketing strategy through online system very popular and the conclusion of this research is Truly Asia as a company need to improve their variant of tour package in order to make tourist more interest to visit the company website. Besides that, increase the cheap price must be accompanied by quality of products to suit with the target, providing accurate information on the website is rather tourist confidence crisis, as well as using the internet connection system that has good quality, in order to minimize system error.
Keywords: Marketing Strategy, Tour Package, Online System